IMPLIKASI PERGANTIAN ANTAR WAKTU (PAW) ANGGOTA DPRD RIAU TERHADAP ADMINSITRASI PARLEMEN - hernimawati, hernimawati (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
This study examines the dynamics and process of PAW process of six members of DPRD Riau period 2014-2019 after deciding to become candidate for regional head. The problems that occurred PAW six Riau DPRD members after the enactment of candidates for regional head in the 2015 election did not run in accordance with established procedures. The research used the concept of Alert Time Substitution and Political Representation Theory with qualitative explorative method. The existing information system within the DPRD still does not reflect the regularity of factors that are shaped by the internal political background of political parties. a very long hiatus meeting in Riau's political representation included some neglected agenda and duties of legislation. In addition, the Ministry of Home Affairs decree was abolished in the determination of PAW Riau DPRD members 2014-2019 and became administrative judges that led to the vacancy of parliamentary seats